Mechanobiological mechanism of cyclic stretch-induced cell columnarization - Lun-Wei Lee; Gang-Hui Lee; I-Hsiu Su; Chia-Hsuan Lu; Keng-Hui Lin; Fu-Lai Wen; Ming-Jer Tang (Cell Reports)
Summary: In vivo, epithelial cells maintain structural integrity under dynamic mechanical perturbations. To study this, we treated various epithelial cell lines with long-term cyclic stretch (CS). Surprisingly, cells transitioned from cuboidal to columnar shape (columnarization) in MDCK cells, while others only elongated. This change correlated with actin accumulation at the top and stress fiber realignment at the bottom. Blocking mechanical stimulation via FAK inhibition or reducing vinculin partially prevented columnarization; however, disrupting tight junctions or cellular contractility substantially blocked it. The MK4 cells, derived from MDCK cells with weaker cell-cell junctions, showed less columnarization under CS, whereas overexpressing Caveolin-1 (Cav1) in MK4 cells enhanced junctions and promoted columnar formation. Atomic force microscopy studies revealed increased apical junctional stiffness in both CS-treated MDCK and Cav1-overexpressing MK4 cells. This, combined with a mathematical model, elucidated the physical characteristics and changes in cell tension post-stretch, revealing the mechanobiological foundation of epithelial cell columnarization.